2002
DOI: 10.1038/sj.ejhg.5200872
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the regulatory and essential myosin light chain genes: genetic variants and mutations in hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) can be caused by mutations in genes encoding for the ventricular myosin essential and regulatory light chains. In contrast to other HCM disease genes, only a few studies describing disease-associated mutations in the myosin light chain genes have been published. Therefore, we aimed to conduct a systematic screening for mutations in the ventricular myosin light chain genes in a group of clinically well-characterised HCM patients. Further, we assessed whether the detected mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 23 publications
2
67
0
2
Order By: Relevance
“…Thus, a mixture of two myosin species having substantially different mechanical capacities can lead to internal stress within the muscle cell, which in turn can result in cellular disarray for the occurrence of HF or sudden death. In patients with rare defects of MLC 1 , MLC 2 and α-TM genes, the mutations induce an increase in Ca 2+ sensitivity and force production (174,(189)(190)(191), leading to hypercontractile myocardium. Increased expression of ALC 1 was observed in the ventricles of patients suffering from fHCM, partially replacing the ventricular isoform VLC 1 .…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Thus, a mixture of two myosin species having substantially different mechanical capacities can lead to internal stress within the muscle cell, which in turn can result in cellular disarray for the occurrence of HF or sudden death. In patients with rare defects of MLC 1 , MLC 2 and α-TM genes, the mutations induce an increase in Ca 2+ sensitivity and force production (174,(189)(190)(191), leading to hypercontractile myocardium. Increased expression of ALC 1 was observed in the ventricles of patients suffering from fHCM, partially replacing the ventricular isoform VLC 1 .…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Recent studies have revealed that the ventricular isoform of myosin regulatory light-chain [RLC; also known as myosin regulatory light-chain 2 (MLRV)] is one of the sarcomeric proteins associated with FHC (Andersen et al, 2001;Flavigny et al, 1998;Kabaeva et al, 2002;Poetter et al, 1996;Richard et al, 2003) (Z. T. Kabaeva, Genetic analysis in hypertrophic cardiomyopathy: missense mutations in the ventricular myosin regulatory light chain gene, PhD thesis, Humboldt Universitat zu Berlin, 2002). The clinical course of FHC is variable and ranges from benign to severe heart failure and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports of MYL2 genetic variations have been published to date. They are A13T (Andersen et al 2001;Hougs et al 2005;Poetter et al 1996), F18L (Flavigny et al 1998;Richard et al 2003), M20L (Olivotto et al 2008), E22K (Garcia-Pavia et al 2011;Kabaeva et al 2002;Poetter et al 1996); I44M (Santos et al 2012), N47K (Andersen et al 2001), G57E (Caleshu et al 2011, R58Q (Flavigny et al 1998;Kabaeva et al 2002;Morner et al 2003;Olivotto et al 2008;Richard et al 2003), P95A (Poetter et al 1996), K104E (Andersen et al 2001), E134A (Di Donna et al 2010;Olivotto et al 2008); D166V, IVS5-2 (an A > G transversion in intron 5 that leads to a premature termination codon) , and IVS6-1 (a G > C transversion in the acceptor splice site of intron 6) (Andersen et al 2001). Recently, a novel sarcomeric protein mutation in the MYL2 gene was identified by exome sequencing in a pedigree with familial dilated cardiomyopathy (DCM) .…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 99%